High throughput combinatorial screening of Cu-Zn-Sn-S thin film libraries for the application of Cu2ZnSnS4 photovoltaic cells - Hutchings, Kyle James (Cranfield University, 2014)
The naturally occurring mineral of Cu2ZnSnS4 (CZTS) is a promising alternative absorber layer for thin film based photovoltaic devices. It has the remarkable advantage that it consists of abundant, inexpensive and non-toxic elements compared to its crystallographically related and highly successful counterparts: the Cu(In,Ga)(S,Se)2 (CIGSSe) and CuIn(S, Se)2 (CISSe) material systems. Therefore, there is real commercial potential for reduced material costs and improved device efficiencies. A two-stage high throughput combinatorial process for the fabrication of Cu-Zn-Sn-S thin film libraries is presented, which consists of either sequentially stacking or co-depositing Cu,Sn and Zn precursor layers by DC magnetron sputtering followed by a sulphurisation process. Sputtering conditions and target-substrate geometry are developed to give compositionally graded Cu-Zn-Sn precursor layers spanning a wide spatial region around the point of stoichiometry. Conversion into Cu-Zn-Sn-S libraries is achieved by thermally evaporating a uniform layer of sulphur directly onto the metal alloy and annealing the sample at 500 °C in a furnace. Effects of the precursor composition on the structural properties of the films prior to the incorporation of sulphur are investigated. The sulphurised libraries are then studied by Scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopy as a function of composition, to assess the effects on morphology and phase formation. Observations of changes in lattice parameters and crystallinity are clear. The opto-electronic and electrical properties of the CZTS film libraries are measured using photoconductivity and hot point probe techniques, respectively. Changes in the band gap and conductivity type are studied as a function of atomic ratios. Based on high performing compositions, devices have been fabricated with the highest achieving cell at 1.26 %. The observations are discussed in the context of the particular compositions and synthesis conditions, and recommendations are made for further work.
Keywords: Photovoltaic cells; Thin films; Dynamic combinatorial library